Muscle fatigue in fibromyalgia is in the brain, not in the muscles: a case–control study of perceived versus objective muscle fatigue. Issue 6 (8th December 2012) - Bandak, Elisabeth; Amris, Kirstine; Bliddal, Henning; Danneskiold-Samsøe, Bente; Henriksen, Marius
Abstract : Objective: To investigate relationships between perceived and objectively measured muscle fatigue during exhausting muscle contractions in women with fibromyalgia (FM) compared with healthy controls (HC). Methods: Women with FM and HC completed an isometric muscle exhaustion task at 90° shoulder abduction. Surface electromyographic (EMG) activity in the deltoid muscle was recorded together with self-reported level of muscle fatigue. Results: 25 participants with FM and 23 HC were included. Average time to exhaustion was 254 s shorter in participants with FM than in HC. Participants with FM did not exhibit the same level of objective signs of muscle fatigue, seen as fewer changes in the EMG activity, as the HC during the exhaustion task. The task did not provoke pain in the HC, while participants with FM reported a doubling of pain. Conclusions: Women with FM had shorter exhaustion times and showed fewer objective signs of muscle fatigue during an exhausting isometric shoulder abduction compared with younger HC. This indicates that perceived muscle fatigue may be of central origin and supports the notion of central nervous dysfunction as basic pathological changes in FM.